Study on the Ductility Behavior of Reinforced Concrete Columns with 10 mm Shear Reinforcement Diameter under Variable Axial Loads - Aldivonso Tambunan; Hasibuan, Samsul Abdul Rahman Sidik (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2025)
Understanding the ductility behavior of reinforced concrete columns is critical for ensuring structural safety in seismic regions, yet there remains limited research on the specific effects of shear reinforcement diameter under varying axial loads. This research investigates the ductility behavior of reinforced concrete columns with a 10 mm shear reinforcement diameter under varying axial loads of 1000 kN, 2500 kN, and 5000 kN. The study aims to understand the effect of shear reinforcement on the ductility of columns and how varying axial loads influence their performance. Numerical modeling was performed using Xtract software, with columns designed to have dimensions of 600 mm x 600 mm (unconfined) and 450 mm x 450 mm (confined). The study focuses on key parameters such as curvature at initial load, curvature at first yield, ultimate curvature, and moment-curvature relationships. The results show that as the axial load increases, the curvature ductility decreases, with the column under 1000 kN demonstrating the highest ductility and the column under 5000 kN showing the lowest. The findings highlight the significant role of shear reinforcement in enhancing the ductility of columns, suggesting that optimal reinforcement design is crucial for ensuring structural resilience under variable loading conditions.